If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11y + -4 = x Reorder the terms: -4 + 11y = x Solving -4 + 11y = x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 11y = 4 + x Combine like terms: -4 + 4 = 0 0 + 11y = 4 + x 11y = 4 + x Divide each side by '11'. y = 0.3636363636 + 0.09090909091x Simplifying y = 0.3636363636 + 0.09090909091x
| 10/12=b/6 | | -4x(4x-1)=0 | | (-4.2x^4)(3x^7)= | | 7/y=49/98 | | 92-y=x | | y=7500-9.5(8000) | | y=7500-9.5(10000) | | 25m=75 | | y=75000+9.5x | | 27+8=10 | | 4(C-9)C=15 | | 31=p-91 | | k*k=36 | | 40*2=r | | 3x-3=1+2x | | x*-10(x-1)=-11 | | 3x-3=9-6x | | 9x^2+3x-50=0 | | 90+0.1x=100 | | 90+0.1x=95 | | a+5=5 | | 99+0.1x=90 | | c-14=6 | | 6(10x-13)=222 | | -12/3x-41/7 | | 16-s=20 | | -6+w/3=-8 | | -36=p-01 | | 4a-4=-2 | | 5/1211/18 | | 3x^4-6x^3+3x^2=0 | | x(6-4)+3=15 |